2015
DOI: 10.2147/ijn.s77081
|View full text |Cite
|
Sign up to set email alerts
|

Non-chemotoxic induction of cancer cell death using magnetic nanowires

Abstract: In this paper, we show that magnetic nanowires with weak magnetic fields and low frequencies can induce cell death via a mechanism that does not involve heat production. We incubated colon cancer cells with two concentrations (2.4 and 12 μg/mL) of nickel nanowires that were 35 nm in diameter and exposed the cells and nanowires to an alternating magnetic field (0.5 mT and 1 Hz or 1 kHz) for 10 or 30 minutes. This low-power field exerted a force on the magnetic nanowires, causing a mechanical disturbance to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 65 publications
4
98
0
Order By: Relevance
“…Similarly, an alternating current magnetic field has been proven to increase the inflammation of cells with internalized Ni NWs due to an increase in the pro-inflammatory cytokine interleukin-6 (Choi et al 2012). More recently, it has been shown that Ni NWs can be used to kill cancer cells with extremely low magnetic fields and frequencies (Contreras et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an alternating current magnetic field has been proven to increase the inflammation of cells with internalized Ni NWs due to an increase in the pro-inflammatory cytokine interleukin-6 (Choi et al 2012). More recently, it has been shown that Ni NWs can be used to kill cancer cells with extremely low magnetic fields and frequencies (Contreras et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the micro-scale magnetic materials, nanomaterials are easily internalized by cells 39, and the intracellular cell membrane destruction has been proven to be more efficient than the disruption from the cell surface 23. Furthermore, the magnetic field in this study is safe and its frequency substantially lower than the risk level in adults 40.…”
Section: Introductionmentioning
confidence: 84%
“…We model this interaction using a quasi-static Stoner-Wohlfarth-like model 20, 21 . Usually, dynamic models are used 4, 14 , but the large torques involved here mean that the retarding effect of the fluid drag is negligible (see supplementary material) and so the particle is assumed to be able to reach the minimum energy configuration on the timescales of the experiment. In this model the energy for a magnetic disc of moment m is given by:where H is the applied field, H k is the anisotropy field, α is the angle of the applied field relative to the easy axis and θ is the angle of the magnetization relative to the easy axis.…”
Section: Estimating Magnetic Torques For the Two Particlesmentioning
confidence: 99%